2014
DOI: 10.1590/0104-1428.1589
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable bags for the production of plant seedlings

Abstract: Abstract:The production of plant seedlings has traditionally used polyethylene bags, which are thrown out in the soil or burned after transplant because the large amount of organic material attached to the bags makes recycling difficult. Additionally, when a seedling is taken from the bag for transplant, there is the risk of root damage, which compromises the plant's development. In this study, we developed biodegradable bags to be used in seedling production, and we verify their influence on the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 12 publications
0
12
0
2
Order By: Relevance
“…Several authors have evaluated active packaging containing α‐tocopherol (α‐TOC) as an antioxidant 17 . However, there is a lack of studies concerning starch/PBAT blends incorporated with α‐TOC, which has been shown to be an eco‐friendly material with interesting performance as food packaging 13,18 …”
Section: Introductionmentioning
confidence: 99%
“…Several authors have evaluated active packaging containing α‐tocopherol (α‐TOC) as an antioxidant 17 . However, there is a lack of studies concerning starch/PBAT blends incorporated with α‐TOC, which has been shown to be an eco‐friendly material with interesting performance as food packaging 13,18 …”
Section: Introductionmentioning
confidence: 99%
“…This is because the roots absorb nutrients from the soil affecting plant height. As research, the PE bags were complete and lacked any signs of decomposition or tearing, with only a few holes that were caused by root growth and could damage the root condition [7,39] studied the biodegradation of blends of ATp and PEBD in activated mud during a 45 d period and found that the pure PEBD films did not lose mass, whereas the blends with 32% and 68% ATp lost 39% and 92% mass, respectively.…”
Section: Total Of Rootsmentioning
confidence: 99%
“…Nowadays, many organic polybags have been developed which are used as planting media, such as viz. root trainers container for Indians sandalwood (Santalum album L.) seedlings [6] , Black and white biodegradable bags for Brazilian ginseng seedling (Pfaffia glomerata (Spreng) Pedersen) [7] , containers made from newspapers, corn starch, palm, cotton, paper, clay and cow dung (Bio-decomposable (Jiffy) Pots) [8] , and biodegradable cellulose paper for small-scale tree nurseries [9] .…”
Section: Introduction mentioning
confidence: 99%
“…1,4,42 No caso de produtos alimentícios e seu devido armazenamento, alguns fatores e propriedades específicas para utilização de embalagens poliméricas devem ser levados em consideração, tais como permeabilidade a gases e vapores de água, a fim de evitar a contaminação através da exposição a diferentes ambientes, preservando suas características e aumentando o tempo de consumo. …”
Section: Propriedades De Barreira E Permeabilidadeunclassified
“…[1][2][3][4][5][6] A degradação de polímeros biodegradáveis ocorre através da ação de microrganismos tais como bactérias, fungos e algas de ocorrência natural. 7 Os polímeros biodegradáveis podem ser obtidos de forma natural durante os ciclos de crescimento de organismos vivos, ou podem ser sintetizados.…”
Section: Introductionunclassified